Mutual coupling and synchronization of optically coupled quantum-dot micropillar lasers at ultra-low light levels - Sören Kreinberg (Nature Portfolio, 2019)
The synchronisation of optical cavities in the quantum regime is still relatively unexplored. Here, Kreinberg et al. investigate the coupling behaviour of two quantum dot microlasers and find that spontaneous emission noise from cavity QED effects plays an important role.